Spatial Suitability of Plant Production Patterns in Al-Rifai District - Jabir, Dr.Majid Abdullah (Thi Qar Arts Journal, 2025)
The research aims to develop a cartographic algorithm for the spatial suitability of agricultural innovation patterns, ranging from lighting to designated categories. To achieve this goal, Geographic Information Systems (GIS) technology was used, specifically Arc Map 10.9. The study is divided into two sections: the first focuses on studying the natural and human geographical factors and their role in natural suitability, while the second examines the spatial suitability model for different types of agricultural production in Al-Rifai District, followed by interpretations and implications. The study proposed scientific hypotheses and was based on systematic performance. Upon completion, the study identified three types of spatial suitability: the first type is highly preferred, the second type is moderately preferred, and the third type is suitable for partial preference. The research aims to create a cartographic model for spatial suitability of production patterns, using GIS technology and Arc Map 10.9. The study is divided into two sections: the first addresses the natural and human geographical factors in spatial suitability, while the second focuses on the spatial suitability model for food production patterns in Al-Rifai District, followed by proposed conclusions. The study adopted scientific hypotheses and addressed the fundamental educational stages. The study concluded that there are three types of spatial suitability: the first type is highly suitable, the second type is moderately suitable, and the third type is suitable for partial preference.